1988
DOI: 10.1159/000226553
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Serum Phosphohexose Isomerase in Gastrointestinal Cancer at Different Stages

Abstract: The purpose of this study was to reevaluate the significance of serum PHI in gastrointestinal cancer at histopathologically defined stages prior to primary treatment. A total of 248 patients with malignant tumors of the gastrointestinal tract and a collective of 42 patients with noncancerous diseases were studied. The results are compared with those obtained with the established markers tissue polypeptide antigen (TPA) and carcinoembryonic antigen (CEA). Phosphohexose isomerase (PHI) revealed an overall diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 3 publications
1
6
2
Order By: Relevance
“…From the mean and the standard deviation obtained, a cutoff level of 39 U/l was established, with false positive results in this group being less than 3%. This upper limit of 39 U/l was confirmed over a 2-year period of clinical application [19,20] and agrees with the re sults of Schwartz [21 ]. Since there are no reports on a serum cutoff level for HK, a value of 2 U/l was estab lished.…”
Section: Correlation O F Enzyme Activities In Normal and Tumor Tissuesupporting
confidence: 89%
See 1 more Smart Citation
“…From the mean and the standard deviation obtained, a cutoff level of 39 U/l was established, with false positive results in this group being less than 3%. This upper limit of 39 U/l was confirmed over a 2-year period of clinical application [19,20] and agrees with the re sults of Schwartz [21 ]. Since there are no reports on a serum cutoff level for HK, a value of 2 U/l was estab lished.…”
Section: Correlation O F Enzyme Activities In Normal and Tumor Tissuesupporting
confidence: 89%
“…Enhanced glycolytic enzyme activities could already be found in early stages with out metastases and in well-differentiated tu mors. Thus, only serum PHI activities [19,20] but not tissue enzyme activities provide information about the extent of the malig nancy.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression and secretion of AMF/PGI by tumor cells induce autocrine stimulation of tumor cell motility, cell transformation and tumorigenicity; 15 elevated circulating AMF/PGI levels are found in the serum of cancer patients. 34,35 AMF/PGI protects against chemotherapeutic agents in vitro as well as in implanted tumors wherein it protects against paclitaxelmediated cell death. 25,36 AMF/PGI interaction with gp78/ AMFR may therefore contribute to tumor cell survival and resistance to chemotherapy by limiting the ER stress response of tumor cells growing in the harsh conditions of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that PHI increases in patients with cancer [5][6][7][8][9][10]. The value of PHI as a tumor marker is of partic ular interest since Chaput et al [ 12] and Faik et al [13] reported that PHI functions as a trophic factor related to proliferation and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Since Warburg's [1] observation of the increased glycolytic activity in tumor cells, numerous reports have described the use of different glycolytic enzymes as tumor markers [2][3][4], From the earliest studies of Bodansky [5] and Schwartz et al [6], PHI appears to be an interesting tumor marker. More recently, other authors have reported new results regarding the use of PHI in dif ferent tumors [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%